Marksomyia, a new subgenus of Culicoides Latreille (Diptera: Ceratopogonidae) from the Australasian biogeographic region with descriptions of two new species - Bellis, Glenn; Dyce, Alan (Zootaxa, 2011)
Marksomyia is proposed as a new subgenus of the genus Culicoides Latreille to embrace six species from Australia and New Guinea. Comparative descriptions of males and females of C. zentae sp. nov. and C. kayi sp. nov., pupae of C. zentae and redescriptions of C. marksi Lee & Reye, C. dycei Lee & Reye, C. parvimaculatus Lee & Reye and C. pseudostigmaticus Tokunaga are presented together with distributional data and keys for their specific determination. The designated type species of the subgenus is C. marksi. Marksomyia is further subdivided into three species complexes based on the shape and sclerotisation of the spermathecae.